The effects of IL-10 gene polymorphism on serum, and gingival crevicular fluid levels of IL-6 and IL-10 in chronic periodontitis - Hulya Toker; Emine Pirim Gorgun; Ertan Mahir Korkmaz; Hatice Balci Yüce; Omer Poyraz (University of São Paulo, 2018)
Abstract Objective Anti-inflammatory cytokines play a crucial role in periodontitis by inhibiting synthesis of pro-inflammatory cytokines. The purpose of this study was to evaluate the effect of interleukin-10 (-597) gene polymorphism and genotype distributions on chronic periodontitis (CP) development and IL-6 and IL-10 levels in gingival crevicular fluid (GCF) and serum before and after non-surgical periodontal treatment. Material and Methods The study population consisted of 55 severe generalized CP patients as CP group and 50 healthy individuals as control group. Plaque index, gingival index, probing depth and clinical attachment level were recorded and GCF and blood samples were taken at both the baseline and the sixth week after non-surgical periodontal treatment. PCR-RFLP procedure was used for gene analyses and cytokine levels were measured via ELISA. Results IL-10 genotype distribution was significantly different between CP and control groups (p=0.000, OR:7, 95%CI, 2.83-60.25). Clinical measurements significantly improved in the CP group after periodontal treatment (p<0.05). Periodontal treatment significantly decreased GCF IL-6 and IL-10 levels. No significant difference was found in clinical parameters between IL-10 AA and AC+CC genotypes at both the baseline and the sixth week (p>0.05). Sixth week GCF IL-10 levels were significantly lower in patients carrying IL-10 AC+CC genotype compared to the patients carrying IL-10 AA genotype (p<0.05). Serum IL-6 and IL-10 levels were lower in patients carrying the IL-10 AA genotype compared to patients with IL-10 AC+CC genotype, but the difference was not significant (p>0.05). Conclusion IL-10 AA genotype carriers had lower IL-6 and IL-6/10 levels in serum; however, GCF IL-6/10 levels were similar in both genotypes. Within the limitations of our study, a possible association between IL-10(-597) gene polymorphism and CP might be considered.